2022
DOI: 10.1038/s41598-022-11433-z
|View full text |Cite|
|
Sign up to set email alerts
|

Characterising the unity and diversity of executive functions in a within-subject fMRI study

Abstract: Behavioural studies investigating the relationship between Executive Functions (EFs) demonstrated evidence that different EFs are correlated with each other, but also that they are partially independent from each other. Neuroimaging studies investigating such an interrelationship with respect to the functional neuroanatomical correlates are sparse and have revealed inconsistent findings. To address this question, we created four tasks derived from the same basic paradigm, one each for updating, inhibition, swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
2
13
0
1
Order By: Relevance
“…Traditional approaches of functional magnetic resonance imaging (fMRI) in healthy participants have also struggled to provide clearer answers. On the one hand, meta-analysis and within-subject studies employing executive tasks targeting two or more putative executive components show overlapping frontal and parietal activations (Niendam et al 2012; Fedorenko et al 2013; Nee et al 2013; Lemire-Rodger et al 2019; Braver et al 2021; Friedman and Robbins 2022; Saylik et al 2022). The activations usually occupy areas in the lateral and dorso-medial frontal cortices, insula, intraparietal sulcus and occipito-temporal junction.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional approaches of functional magnetic resonance imaging (fMRI) in healthy participants have also struggled to provide clearer answers. On the one hand, meta-analysis and within-subject studies employing executive tasks targeting two or more putative executive components show overlapping frontal and parietal activations (Niendam et al 2012; Fedorenko et al 2013; Nee et al 2013; Lemire-Rodger et al 2019; Braver et al 2021; Friedman and Robbins 2022; Saylik et al 2022). The activations usually occupy areas in the lateral and dorso-medial frontal cortices, insula, intraparietal sulcus and occipito-temporal junction.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying early deficits is important as it facilitates early detection and possible treatment of a condition. In a recent study, Saylik et al (2022) reported in a functional magnetic resonance imaging (fMRI) study that all four EFs activated an overlapping set of brain areas (unity) particularly in the PFC, but also distinct areas (diversity). Thus, the different decline rates observed in this study could be linked with these unique regions activated during the specific EF processing which may also be linked to the central executive system (CES) of the WM model proposed by Baddeley and Hitch (1974).…”
Section: Discussionmentioning
confidence: 99%
“…There have been suggestions that dual-tasking constitutes an EF on its own, separate from EFs such as switching, updating, and inhibition ( Miyake et al, 2000 ; Strobach et al, 2014 ), although strong evidence in support of this is sparse. Opposed to these suggestions, we recently have shown that the additional processes demanded in PRP tasks are strongly linked to the EF of working memory ( Otermans et al, 2021 ), and, in an fMRI study, that there is profound overlap in the brain areas associated with dual-task coordination (PRP task), inhibition (Stroop task), switching (Task switching), and updating (n-back task) ( Saylik et al, in press ). But even if dual-tasking is considered a distinct EF, this does not mean that a specific implementation of a dual-task, such as the PRP task, may not also demand other EF, such as switching, inhibition, and/or updating.…”
Section: Discussionmentioning
confidence: 99%
“…The active scheduling approach is also supported by neuroimaging data ( Marois and Ivanoff, 2005 ). For example, several studies employing functional magnetic resonance imaging (fMRI) have shown that performance of a PRP dual-task activates lateral-prefrontal cortices (lPFC) over-additively more than predicted by the sum of the component tasks ( Saylik et al, in press ; Szameitat et al, 2002 ; Schubert and Szameitat, 2003 ; Stelzel et al, 2009 ), and that the lPFC is stronger activated if the order in which the participants have to respond to the task switches from one trial to the next as compared to when it stays constant ( Szameitat et al, 2006 ; Stelzel et al, 2008 ). Furthermore, Stelzel et al (2008) were able to demonstrate that the lPFC areas activated by dual-task coordination can be differentiated from the lPFC areas linked to the maintenance of the task-set [see also Strobach et al (2021a) for a similar conclusion based on behavioral findings].…”
Section: Introductionmentioning
confidence: 99%